Fonologi Bahasa Palembang pada Video Kanal YouTube WIKITONGUES: Ihsan and Septiadi speaking Palembangnese - Fikri Fikri; Dyta Septiyatik; Mudhiah Umamah (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to look at the form of phonetic transcription in Palembang Malay language and what is contained in the sounds of Palembang Malay on Wikitongues YouTube video channel. The research applied qualitative descriptive approach by utilizing qualitative data. The source of the data is the sound utterances spoken by two native speakers from Palembang on the YouTube channel entitled WIKITONGUES: Ihsan and Septiadi speaking Palembangnese. The results of the study showed that there are 25 phonemes consisting of six vowel phonemes and 19 consonant phonemes in Palembang Malay language according to the video. As well, there are 8 places of articulation of phonemes and 7 ways of articulation of Palembang Malay phonemes. It can be concluded that Palembang Malay has almost complex sound phonetics and even has minimal allophones and pairs, although only seen from the perspective of a short video on the Wikitongues youtube channel.